Jade culture of China: linguistic aspect - Hu, Jiadong (Journal of the Belarusian State University. Philology, 2020)
Jade culture is an important component of traditional Chinese culture; its name is associated with the name of the mineral, which since ancient times has been considered one of the unofficial symbols of China. Despite the fact that the jade culture of China dates back many centuries, the term jade culture was introduced into scientific circulation relatively recently – in the 1990s, when a systematic study of linguistic means containing the semantic component of jade began in Chinese linguistics. In Russian-language scientific literature, the linguistic aspects of jade culture have not been considered theoretically to date. The article provides an overview of Chinese scientific literature on the problems of jade culture; the difficulties of translating into Russian the words and idiomatic expressions containing the semantic component of jade are shown, the results of statistical analysis of dictionary data – the words and idiomatic expressions of the modern Chinese language containing the specified semantic component are presented.